Influence of Materialism, Social Status Display and Brand Consciousness on Status consumption among working women in Klang Valley - Sukjeet Kaur, Sandhu; Laily, Paim; Kamaljeet, Kaur (INTI International University, 2018)
The study measures the influence of materialism, social status display and brand consciousness on status consumption among working women in Klang Valley. A total of 410 working women completed the questionnaire which were collected using mall intercept method. The focus on luxury branded items was narrowed down to three categories which were clothing/scarfs, shoes and handbags. The results revealed that materialism, social status display and brand consciousness has a significant relationship with status consumption.